Nitrification of a tropical peat soil cultivated with oil palm (Elaeis guineensis Jacq.) - Ariffin, Mohd Rizal (2017)
As knowledge on nitrogen (N) cycle is evolving rapidly, soil nitrification has become the centre of research interest because it is the single most important process in the N-cycle that leads to N losses in broad range of environments. With further expansion of oil palm on tropical peat lands, N cycling is predicted to be modified. However, very few current literatures reported nitrification in tropical peat soils cultivated with oil palm. Therefore, there is a need to understand the nitrification process in cultivated tropical peat soils with oil palm.